How Does the Gender and Attractiveness of the Supervisor Influence the Performance of Supervisees? Implications for Hiring Processes in New Ventures - Koellinger, Philipp; Block, Joern H. (Senate Hall, 2016)
A series of field and laboratory experiments were conducted in which single-sex groups of male or female students competed in different intellectual tasks to earn money or university grades (N = 291). The supervisor of these groups was one of several young and attractive males or females. The results show that when the supervisor was a female, the performance of male participants was, on average, negatively influenced. Group size moderated this effect such that having a female supervisor produced a negative effect in small groups and a positive effect in large groups of male supervisees. Implications of the findings for the hiring processes in new ventures are discussed. Keywords: supervision, mixed-sex interaction, performance, entrepreneurial leadership, hiring processes PsycINFO codes: 2340, 2970, 3620
Keywords: supervision|mixed-sex interaction|performance|entrepreneurial leadership|hiring processes